Ex vivo characterization of acute myeloid leukemia patients undergoing hypomethylating agents and venetoclax regimen reveals a venetoclax-specific effect on non-suppressive regulatory T cells and bona fide PD-1+TIM3+ exhausted CD8+ T cells - Corradi, Giulia; Forte, Dorian; Cristiano, Gianluca; Polimeno, Andrea; Ciciarello, Marilena; Salvestrini, Valentina; Bandini, Lorenza; Robustelli, Valentina; Ottaviani, Emanuela; Cavo, Michele; Ocadlikova, Darina; Curti, Antonio (Frontiers in Immunology, 2024)
Acute myeloid leukemia (AML) is an aggressive heterogeneous disease characterized by several alterations of the immune system prompting disease progression and treatment response. The therapies available for AML can affect lymphocyte function, limiting the efficacy of immunotherapy while hindering leukemia-specific immune reactions. Recently, the treatment based on Venetoclax (VEN), a specific B-cell lymphoma 2 (BCL-2) inhibitor, in combination with hypomethylating agents (HMAs) or low-dose cytarabine, has emerged as a promising clinical strategy in AML. To better understand the immunological effect of VEN treatment, we characterized the phenotype and immune checkpoint (IC) receptors' expression on CD4 + and CD8 + T cells from AML patients after the first and second cycle of HMA in combination with VEN.HMA and VEN treatment significantly increased the percentage of naïve CD8 + T cells and TIM-3 + CD4 + and CD8 + T cells and reduced cytokine-secreting non-suppressive T regulatory cells (Tregs).Of note, a comparison between AML patients treated with HMA only and HMA in combination with VEN revealed the specific contribution of VEN in modulating the immune cell repertoire.Indeed, the reduction of cytokine-secreting non-suppressive Tregs, the increased TIM-3 expression on CD8 + T cells, and the reduced co-expression of PD-1 and TIM-3 on both CD4 + and CD8 + T cells are all VEN-specific. Collectively, our study shed light on immune modulation induced by VEN treatment, providing the rationale for a novel therapeutic combination of VEN and IC inhibitors in AML patients.